The regional impact of a CO2 tax on gasoline demand: a spatial econometric approach - Massimo Filippini; Fabian Heimsch (ETH Zurich, CER-ETH - Center of Economic Research, 2015)
In order to mitigate climate change, several countries around the world have introduced or are planning a CO2 tax on energy consumption. The effectiveness of such a tax depends on the level of the short- and long-run price elasticity. Moreover, acceptance of a CO2 tax by a society depends on both the distributional effects of such a tax among households and its spatial effects among regions. In this paper, the regional impact of a hypothetical CO2 tax on gasoline consumption in Switzerland is analysed by estimating a demand function for gasoline using panel data from 547 Swiss municipalities from 2001 to 2008. Gasoline sales were collected from the five largest gasoline companies operating in Switzerland, covering about 60% of overall sales. Swiss municipalities are relatively small units, and car ownership and use in one municipality is thought to influence gasoline sales in the neighbouring ones. Accordingly, the method used in the model also accounts for spatial correlation in the consumption of gasoline. Overall, our spatial econometric analysis shows that the tax burden of a CO2 tax will be higher in rural areas than in urban areas.
Keywords: D; D2; Q; Q4; R2; 330; gasoline demand; aggregate panel data; spatial economic effect; spatial econometrics